Pelatihan Kewirausahaan untuk Menghasilkan Ide Bisnis Inovatif bagi Siswa SMK - Ida Bagus Ardhi Putra; I Made Dwi Hita Darmawan; Kurniawan Joko Purnomo (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Entrepreneurship is one of the important elements in economic growth in Indonesia when viewed from the number of vocational high school (SMK) graduates who do not get jobs. An Entrepreneurship Seminar was held at SMK Bali Dewata Denpasar with the theme